2020
DOI: 10.3389/fmicb.2020.579389
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Factors Correlate With Antimicrobial Resistance Among Clinical Proteus mirabilis Strains

Abstract: Proteus mirabilis is the third most common etiological factor of urinary tract infection. It produces urease, which contributes to the formation of a crystalline biofilm, considered to be one of the most important virulence factors of P. mirabilis strains, along with their ability to swarm on a solid surface. The aim of this study was to analyze the pathogenic properties of two selected groups of clinical P. mirabilis isolates, antimicrobial susceptible and multidrug resistant (MDR), collected from hospitals i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 85 publications
0
12
1
Order By: Relevance
“…Proteus mirabilis is the 4 th cause of urinary tract infections in women [38] and males [12], and like other germs, their resistance to antimicrobials increases drastically [37]. A recent study evaluated its resistance regarding forming biofilmsstable biofilms mean higher resistance [21]. Studies in Ghana have confirmed the resistance of Proteus mirabilis to cotrimoxazole (81%) and ampicillin (77%) [20], different data from ours: cotrimoxazole 71.42% and ampicillin 28.57%.…”
Section: Resultsmentioning
confidence: 68%
“…Proteus mirabilis is the 4 th cause of urinary tract infections in women [38] and males [12], and like other germs, their resistance to antimicrobials increases drastically [37]. A recent study evaluated its resistance regarding forming biofilmsstable biofilms mean higher resistance [21]. Studies in Ghana have confirmed the resistance of Proteus mirabilis to cotrimoxazole (81%) and ampicillin (77%) [20], different data from ours: cotrimoxazole 71.42% and ampicillin 28.57%.…”
Section: Resultsmentioning
confidence: 68%
“…Concerning the correlation between the antimicrobial resistance genes and the virulence determinants, a previous study that was reported by Filipiak 64 revealed an inversed correlation between the virulence factors and the presence of the resistance genes in the retrieved P. mirabilis strains. However, in the present study, the majority of the screened virulence genes were found in the recovered isolates.…”
Section: Discussionmentioning
confidence: 82%
“…A high percentage of the isolates were found to be resistant to ampicillin, ampicillin/sulbactam, cefotaxime, gentamicin, and nitrofurantoin. In the literature data, there are many reports about bacterial resistance to SXT, β-lactams, fluoroquinolones, nitrofurantoin, fosfomycin, aminoglycosides, tetracyclines, and sulfonamides [ 30 , 31 , 32 , 33 ]. Due to this phenomenon, there is a need to explore other effective and alternative drugs for the treatment of UTIs and their complications.…”
Section: Discussionmentioning
confidence: 99%